10th Workshop on Biomedical and Bioinformatics Challenges for Computer Science - BBC2017 - Agapito, Giuseppe (2021)
Agapito, G., Cannataro, M., Castelli, M., Dondi, R., & Zoppis, I. (2017). 10th Workshop on Biomedical and Bioinformatics Challenges for Computer Science - BBC2017. Procedia Computer Science, 108, 1113-1114. https://doi.org/10.1016/j.procs.2017.05.279